Biomedical Translational Research From Disease Diagnosis to Treatment - Sobti, R.C.; Ganju, Awtar Krishan (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The second volume of the Biomedical translational research discusses advancements in biomedical research for understanding the pathophysiology of various diseases towards improving diagnosis and treatment. It presents the integration of molecular-based technologies, clinical genomics, and medical informatics to improve diagnostic and treatment strategies. Further, the book reviews molecular genomics approaches for diagnosis and managing tuberculosis. It also covers the innovative strategies for cancer treatment through targeting metabolic pathways, tumor microenvironment, cancer stem cells, and immune cells. It also illuminates novel strategies for heart failure diagnosis and therapeutic approaches for the treatment of heart failure. It discusses improvements in translational research for discovery of new diagnostic tests, identifying novel biomarkers and drugable targets, and predicting optimal treatments based on understanding the underlying molecular basis of the disease. Lastly, it reviews the preclinical models of restenosis and their application and limitation in the evaluation of device-based interventional technologies for the treatment of coronary artery diseases.
Chapter 1. Age-Rage Stress In The Pathophysiology Of Atherosclerosis And Its Treatment -- Chapter 2. Stem Cells In Dermatology: What The Future May Hold -- Chapter 3. Current Advances And Future Avenues In Endocrinology -- Chapter 4. Autologous Conditioned Serum In Lumbar And Cervical Radiculopathy: A Systematic Review -- Chapter 5. Bench To Bedside In Ophthalmology -- Chapter 6. Rapid Eye Movement In Sleep And Dream Sleep -- Chapter 7. Novel Cellular-Stress Models With Implications In Understanding And Treating Ent Pathologies -- Chapter 8. Respiratory Disorders : Contemporary Issues In 2020 -- Chapter 9. Discovery Of Hepatitis Viruses And Two Nobel Prizes : A Tale Of Observations Serendipity Collaboration Research Institute Inter Predated And Game Changing Innovation. Chapter 10. Conventional And Modern Approaches For Clinical And Laboratory Diagnosis Of Tuberculosis -- Chapter 11. Gut Microbes In Cardiovascular Diseases -- Chapter 12. Heart Failure - Future Perspectives -- Chapter 13. IL-10 : A Key Molecular In The Mitigation Of Heart Failure -- Chapter 14. Gene Therapy In Liver Disease : Challenges And Outcomes -- Chapter 15. Interrupting Crystal To Calculus Conversion : The Future Of Research In Urolithiasis -- Chapter 16. Stem Cells - Medical Marvel In Management Of Kidney Diseases -- Chapter 17. Deciphering The Code Of Male Infertility : Genetic Tests, Counselling And Molecular Basis Of Spermatogenic Failure -- Chapter 18. Translational Epidemiology In Cancer Research : The Less Travelled Path -- Chapter 19. Adenosine Pathway In Genitourinary Malignancies: A Promising Immunotherapeutic Target -- Chapter 20. Immune Checkpoint Inhibitors In Cancer Therapy: A Ray Of Hope -- Chapter 21. Recent Developments In The Immunotherapeutic Approaches For Cancer Treatment. Chapter 22. Thrombotic Complications In Women : Risks And Prevention -- Chapter 23. Biomedical Science And Women Health -- Chapter 24. Advances In The Role Of Macronutrients In Human Health And Diseases.
Keywords: Medicine-Research.; Biology-Research.; Medical genetics; Diagnosis; Molecular biology; Cancer; Biomedical Research; Clinical Genetics; Diagnosis; Molecular Biology; Cancer Biology